2017
DOI: 10.1016/j.orggeochem.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, isotopic and radiocarbon evidence for broomcorn millet cropping in Northeast France since the Bronze Age

Abstract: Molecular and isotopic investigation of lipids from soils filling several structures from an archaeological site located at Obernai (Alsace, NE France) has revealed the presence of miliacin, a triterpenoid marker from Panicum miliaceum (broomcorn millet), indicating that this cereal was cultivated at the site. The concentration profiles of miliacin within silos and its detection in other archaeological structures (e.g. Gaulish pit) suggest that miliacin did not originate from cereals stored in the silos but ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…10 μg g −1 ) of the molecule in this sample was much greater than previously reported (Heron et al, 2016) permitting a stable carbon isotope measurement by GC-C-IRMS. The δ 13 C value of this compound was −20.5‰ which is in excellent agreement with reported values from miliacin directed isolated from millet grains and extracted from soils (Courel et al, 2017;Jacob et al, 2008) and slightly enriched (ca. 3‰) compared to fatty acids extracted from previously reported prehistoric pottery associated with miliacin (Heron et al, 2016).…”
Section: Resultssupporting
confidence: 90%
“…10 μg g −1 ) of the molecule in this sample was much greater than previously reported (Heron et al, 2016) permitting a stable carbon isotope measurement by GC-C-IRMS. The δ 13 C value of this compound was −20.5‰ which is in excellent agreement with reported values from miliacin directed isolated from millet grains and extracted from soils (Courel et al, 2017;Jacob et al, 2008) and slightly enriched (ca. 3‰) compared to fatty acids extracted from previously reported prehistoric pottery associated with miliacin (Heron et al, 2016).…”
Section: Resultssupporting
confidence: 90%
“…Two other isomers, β-amyrin ME (olean-12-en-3β-ol ME) and α-amyrin ME (urs-12-en-3β-ol ME), were also identified from their significant ions m/z at 440, 425, 218, 203 and 189, as well as their relative retention time on nonpolar columns (Han et al 2016, Avataneo andSablier, 2017). These pentacyclic triterpene compounds have all been previously detected in broomcorn millet and utilised as tracer biomarkers for indications of millet cultivation (Bossard et al 2013, Courel et al 2017. Simulated pottery cooking experiments have also revealed that miliacin can move from the millet into the ceramic matrix during the cooking process and, thus, can be used as biomarker for millet processing in pottery (Heron et al 2016).…”
Section: Resultsmentioning
confidence: 97%
“…;Motuzaite- Matuzeviciute et al 2016) and, more recently, in archaeological pottery(Heron et al 2016;Courel et al 2017;Kučera et al 2019), although it should be noted that it is not an African…”
mentioning
confidence: 99%